2009
DOI: 10.1089/aid.2009.0092
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: HIV Type 1 Genetic Diversity among Tea Plantation Workers in Kericho, Kenya

Abstract: In preparation for HIV-1 vaccine trials in Kenya, 2801 study volunteers, from a tea plantation in Kericho, were recruited as part of a prospective vaccine cohort development study. Cryopreserved plasma was available from 401 HIV-positive volunteers, and was the source of viral RNA for genotyping by the multiregion hybridization assay (MHA). Logistic regression was performed to determine association of risk factors and HIV-1 recombinant and dual infections. At baseline, HIV-1 subtype A was the dominant circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The information retrieved from RV148 volunteers included basic sociodemographic characteristics, but the volunteers were not asked questions regarding behaviors that may increase the risk for HIV acquisition (41). In cohorts in Thailand and worldwide, it has been shown that there were associations between the complexity of HIV-1 strains and sociodemographic characteristics and behaviors that may increase the risk of HIV infection (e.g., more frequent needle sharing among IDUs [61], the presence of sexually transmitted infections [63], exchanging sex for money [65,66), and having high numbers of sex partners [66]). We compared the frequency of different molecular forms-pure subtypes and recombinants-between RV148 and other low-risk cohorts (i.e., RV109, a mother-to-child transmission [MTCT] [83]) from Thailand that have also been genotyped using MHAbce.…”
Section: Discussionmentioning
confidence: 99%
“…The information retrieved from RV148 volunteers included basic sociodemographic characteristics, but the volunteers were not asked questions regarding behaviors that may increase the risk for HIV acquisition (41). In cohorts in Thailand and worldwide, it has been shown that there were associations between the complexity of HIV-1 strains and sociodemographic characteristics and behaviors that may increase the risk of HIV infection (e.g., more frequent needle sharing among IDUs [61], the presence of sexually transmitted infections [63], exchanging sex for money [65,66), and having high numbers of sex partners [66]). We compared the frequency of different molecular forms-pure subtypes and recombinants-between RV148 and other low-risk cohorts (i.e., RV109, a mother-to-child transmission [MTCT] [83]) from Thailand that have also been genotyped using MHAbce.…”
Section: Discussionmentioning
confidence: 99%
“…Single infections were defined as the presence of subtypes B, C, or CRF01 AE, or any of the recombinant genotypes. Dual infections were defined as the presence of B/CRF01 AE Dual; C/CRF01 AE Dual; and B/C Dual genotypes following the accepted classification used elsewhere (Arroyo et al, 2005(Arroyo et al, , 2009Herbinger et al, 2006;Hoelscher et al, 2002;Kijak et al, 2007;Saathoff et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In an effort to characterize HIV-1 subtype diversity within a segment of Kenyan society considered to be at community-level risk of infection, the HIV and Malaria Cohort Study was conducted to observe prevalent and incident infections within a community cohort of Tea plantation workers near Kericho, Kenya. The initial phase of the study detected 401 prevalent infections from participants infected prior to 2003 [ 15 ]. Using the multi-region hybridization assay, it was revealed that HIV-1 subtype A represented the majority (56%) of circulating pure subtypes within the prevalent infections of this cohort, followed by subtypes D (10%) and C (5%); the remaining strains were recombinants (29%) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The initial phase of the study detected 401 prevalent infections from participants infected prior to 2003 [ 15 ]. Using the multi-region hybridization assay, it was revealed that HIV-1 subtype A represented the majority (56%) of circulating pure subtypes within the prevalent infections of this cohort, followed by subtypes D (10%) and C (5%); the remaining strains were recombinants (29%) [ 15 ]. The present study describes the subsequent incident phase, wherein HIV-1 negative participants were followed from 2003–2006 in order to identify and characterize incident and early infections [ 16 ].…”
Section: Introductionmentioning
confidence: 99%